2017
DOI: 10.1002/ijc.30567
|View full text |Cite
|
Sign up to set email alerts
|

Biology and therapeutic implications of VEGF-A splice isoforms and single-nucleotide polymorphisms in colorectal cancer

Abstract: Tumor growth, dissemination and metastasis are dependent on angiogenesis. The predominant vascular endothelial growth factor (VEGF) isoform that plays a major role in angiogenesis is VEGF-A. Indeed, VEGF-A is implicated in promoting angiogenesis of numerous solid malignancies, including colorectal cancer (CRC). A large body of preclinical and clinical evidence indicates that the expression of specific VEGF-A isoforms represents a predominant pro-angiogenic factor, which is associated with formation of metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 74 publications
0
34
0
Order By: Relevance
“…This is a CNV region that encompasses the chromatin modifier CHD8, which has been significantly associated with sporadic CRC risk [26]. Regarding the NP group, in 6p21 (one of the most frequently gained regions), VEGFA is located, which encodes a growth factor from the PDGF/VEGF family, responsible for the induction of vascular endothelial cell migration and proliferation, thus playing a pivotal role in angiogenesis, both in physiological and pathological conditions [27]. In one of the most frequently lost regions, in 9p11, microRNA-1299 is encoded, a negative CRC regulator of STAT3 that is essential for cancer progression to advanced malignancy [28].…”
Section: Discussionmentioning
confidence: 99%
“…This is a CNV region that encompasses the chromatin modifier CHD8, which has been significantly associated with sporadic CRC risk [26]. Regarding the NP group, in 6p21 (one of the most frequently gained regions), VEGFA is located, which encodes a growth factor from the PDGF/VEGF family, responsible for the induction of vascular endothelial cell migration and proliferation, thus playing a pivotal role in angiogenesis, both in physiological and pathological conditions [27]. In one of the most frequently lost regions, in 9p11, microRNA-1299 is encoded, a negative CRC regulator of STAT3 that is essential for cancer progression to advanced malignancy [28].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the present study, the associations among EDA + FN, vessels, and bone destruction in radicular cysts were investigated. Bevacizumab [15] or the type II bacterial clustered, regularly interspaced, palindromic repeats (CRISPR)-associated (Cas) system [2,4] was used to block the effects of either VEGF or EDA + FN [16], respectively, and inhibit osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] SNPs are often performed as genetic markers for the prediction of patient response to susceptibility and development of CRC. [ 7 ] A recent polymorphism study showed that the RAD52 rs1051669 AA genotype was associated with a significantly increased risk of developing CRC. [ 8 ] Interestingly, in another genetic study, the functional RAD52 rs7963551 polymorphism contributed to risk susceptibility of hepatitis B virus related hepatocellular carcinoma in Chinese populations.…”
Section: Introductionmentioning
confidence: 99%